La finalité des décisions de la Commission de protection du territoire agricole du Québec : quelques réflexions sur l'affaire Bell Hélicoptères - Glenn, Jane (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
In the Bell Helicopter case, the government intervened under the Act to preserve agricultural land to grant Bell the necessary permission to install a helicopter assembly plant in an agricultural zone near Mirabel Airport notwithstanding a decision to contrary effect by the Commission de protection du territoire agricole du Québec (C.P.T.A.Q.). It did so even though the statute states that such decisions are « final and without appeal ». This article examines the role of the provincial government in protecting agricultural land and suggests several statutory changes that could ensure an effective role to the government while still respecting the independence of the C.P.T.A.Q.